Management of doses from medical exposures in interventional radiology: an integrative review: Gerenciamento das doses decorrentes de exposições médicas na radiologia intervencionista: uma revisão integrativa - Fernando Rockembach Mazuim; Daiane Cristini Barbosa Souza; Alexandre D’Agostini Zottis (Brazilian Journal of Radiation Sciences, 2022)
Interventional radiology (IR) uses minimally invasive image-guided procedures that may require a long duration and deliver high radiation doses to the patient. The most current studies on management and dose reduction in IR have shown to be of fundamental importance in radiation protection practices. The objective of this study was to survey what has been published in the national and international literature on the doses received by patients undergoing IR procedures. It consisted of an integrative review study carried out in Scielo, Pubmed, and INIS databases in the time frame of 2016-2021, using as descriptors: interventional radiology, radiation injuries, radiological protection, dosimetry; and their equivalents in English: interventional radiology, radiation injuries, radiological protection, and dosimetry. The initial sample consisted of 68 full articles related to the theme, published during the study period. Of these, 11 articles were selected and made up the final sample. The results indicate that the use of software in dose management and monitoring has proven to be an important tool in radiological protection. The implementation of dose reduction strategies and increased awareness about the use and effects of radiation result in significantly lower doses to both professionals and patients. No national study on dose management has been identified, highlighting the need to promote the subject in the country. The main recommendations identified were the introduction of technologies and the training of the workers involved.